Pengaruh Pengawasan Keuangan, Penerapan Standar Akuntansi Pemerintah Berbasis Akrual, dan Kualitas Pelatihan terhadap Keterandalan Pelaporan Keuangan - Ni Putu Noviyantini; Sunitha Devi (Universitas Pendidikan Ganesha, 2020)
This research aims to understand the effect of financial control, the implementation of accrual-based government accounting standards, and the quality of training on the reliability of financial reporting. This type of research used is quantitative research. The population in this research is all employees of the financial sub division at 27 SKPD in Badung Regency. The sampling method used is purposive sampling. The number of samples in this research were 108 respondents. This research uses primary data obtained from distributing questionnaires directly to respondents. Data analysis techniques used include descriptive statistical tests, data quality tests, classic assumption tests, and hypothesis testing using multiple linear regression analysis using IBM SPSS Statistics 23. The research results prove that: (1) financial control has a positive and significant effect on reliability finance report; (2) the implementation of accrual-based government accounting standards has a positive and significant effect on the reliability of financial reporting; (3) the quality of training has a positive and significant effect on the reliability of financial reporting.